Refuge ponds increase fish production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Studies on the rice-fish farming system have shown that fish production can be improved when a small pond is constructed adjacent to the rice field. These ponds act as refuges after the rice in harvested. Although rice fish-farming is an old...